Reduced heart rate variability is associated with higher illness burden in bipolar disorder - Ortiz, Abigail; Bradler, Kamil; Moorti, Pooja; MacLean, Stephane; Husain, M Ishrat; Sanches, Marcos; Goldstein, Benjamin I; Alda, Martin; Mulsant, Benoit H (Journal of psychosomatic research, 2021)
BACKGROUND: Bipolar disorder (BD) is associated with premature death and ischemic heart disease is the main cause of excess mortality. Heart rate variability (HRV) predicts mortality in patients with or without cardiovascular disease. While several studies have analyzed the association between HRV and BD, none has analyzed the association of HRV with illness burden in BD. METHODS: 53 participants with BD I and II used a wearable device to assess the association between HRV and factors characterizing illness burden, including illness duration, number and type of previous episode(s), duration of the most severe episode, history of suicide attempts or psychotic symptoms during episodes, and co-morbid psychiatric disorders. We ran unadjusted models and models controlling statistically for age, sex, pharmacotherapy, baseline functional cardiovascular capacity, BMI, years of education, and marital status. We also explored the association between HRV and an overall illness burden index (IBI) integrating all these factors using a weighted geometric mean. RESULTS: Adjusted and unadjusted models had similar results. Longer illness duration, higher number of depressive episodes, longer duration of most severe manic/hypomanic episode, co-morbid anxiety disorders, and family history of suicide were associated with reduced HRV, as was bipolar depression severity in the participants experiencing a depressive episode. Finally, a higher IBI score was associated with lower HRV. CONCLUSIONS: High illness burden is associated with reduced HRV in BD. While the IBI needs to be validated in a larger sample, it may provide an overall measure that captures illness burden in BD.
Keywords: Cost of Illness; bipolární porucha; Anxiety Disorders; osobní újma zaviněná nemocí; pokus o sebevraždu; Heart Rate; Humans; lidé; srdeční frekvence; Suicide, Attempted; Bipolar Disorder; úzkostné poruchy